2015
DOI: 10.1038/ncomms9285
|View full text |Cite
|
Sign up to set email alerts
|

Baleen whales host a unique gut microbiome with similarities to both carnivores and herbivores

Abstract: Mammals host gut microbiomes of immense physiological consequence, but the determinants of diversity in these communities remain poorly understood. Diet appears to be the dominant factor, but host phylogeny also seems to be an important, if unpredictable, correlate. Here we show that baleen whales, which prey on animals (fish and crustaceans), harbor unique gut microbiomes with surprising parallels in functional capacity and higher level taxonomy to those of terrestrial herbivores. These similarities likely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
192
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(216 citation statements)
references
References 57 publications
(86 reference statements)
22
192
2
Order By: Relevance
“…As found previously [10][11][12]14], variation in taxonomic composition among wild Malagasy mammals was correlated with both host evolutionary history and diet, depending on the relatedness of the host species. Moreover, shared terrestriality, but not geographic distance between sampling sites, predicted microbiome similarity among distantly related hosts with divergent diets and digestive physiologies.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As found previously [10][11][12]14], variation in taxonomic composition among wild Malagasy mammals was correlated with both host evolutionary history and diet, depending on the relatedness of the host species. Moreover, shared terrestriality, but not geographic distance between sampling sites, predicted microbiome similarity among distantly related hosts with divergent diets and digestive physiologies.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies of zoo animals reared on artificial diets have claimed that diet and shared environment have greater impacts on gut microbiome composition than endogenous factors [10][11][12][13][14]. Other studies have focused on closely related mammal species and generally found that host species and their gut microbes exhibit concordant relationships [8,[15][16][17][18], with the gut microbial communities of different host species forming distinct clusters [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the skin (Figure 3H), gut and respiratory microbiomes of diverse marine mammal species, and describe species-specific relationships (Johnson et al, 2009;Apprill et al, 2014;Bik et al, 2016). Connections between the community composition of the microbiome and animal health (Apprill et al, 2014) and diet (Nelson et al, 2013;Sanders et al, 2015) have been made, and more detailed studies are needed to understand these specific connections. While there are very limited resources available for studying host-microbiome interactions in marine mammals, there are some animals in captivity as well as well-studied populations that will heighten investigations of host-microbiome symbiosis and dysbiosis in these sentinel species.…”
Section: Overview Of Diverse and Emerging Animal-microbiome Study Sysmentioning
confidence: 99%
“…In terms of assembly, both whole genome shotgun and marker gene guided sequencing have been used on diferent aquatic organisms. The commonly used marker gene in metagenomics analyses is the 16S ribosomal RNA (16S rRNA), which has been widely used to characterize the microbiota of diferent aquatic organisms including rainbow trout [88,89], Atlantic salmon [11,12], turbot (Scophthalmus maximus) [90], lamprey (Lampetra morii) [91] and Baleen whale [92]. Whole genome shotgun sequencing has also been widely used in the study of environmental microbial communities and pathogens infecting diferent aquatic organisms.…”
Section: Metagenomics Technologies and Their Limitationsmentioning
confidence: 99%